PERAMALAN PENJUALAN MAKANAN KERING TOKO IKM MART JOMBANG MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING BERBASIS WEB - Fatimatuz Zahro , Siti; Setyo Permadi , Ginanjar (Inovate, 2024)
The IKM Mart Jombang store was chosen as the object of research study because sales at this company show a consistent growth trend every year. To deal with uncertainty and assist in decision making, the Double Exponential Smoothing method is used. This method has the advantage of handling situations with limited data and providing fairly accurate forecasting results. However, this method also has weaknesses, namely the difficulty in carrying out maintenance on a large scale. Because the Smoothing process is carried out twice, parameter maintenance is required so that the forecasting results remain accurate. Based on analysis with an alpha value of 0.3 on dry food sales with the smallest MSE value, namely alpha 0.3. In a comparison between system sales and dry food sales, system sales produce less scrap than dry food sales. For one year, from January 2022 to December 2022, testing the accuracy of dry food sales reached an average accuracy of 86%. Keywords: forecasting, Double Exponential Smoothing, sales